Efektivitas kebiasaan pagi dalam meningkatkan kecerdasan emosional siswa di Mts al-Hidaya Donowarih Karangploso - Aulia Shofia Rasida; Nury Firdausia (Journal Islamic Studies, 2025)
Intellectual intelligence alone will not be enough to support students to understand every learning delivered by the teacher. In addition to intellectual intelligence, emotional intelligence is also needed to support the learning process, of course, this is inseparable from the role of teachers, parents, and the surrounding environment. To stimulate the increase in emotional intelligence, it is necessary to integrate character formation and the implementation of supporting activities in schools which are arranged into weekly, monthly, and even yearly activity programs. With this research, it is hoped that this goal can be achieved by identifying through related variables, namely whether there is an influence of the morning habituation program on the improvement of students' emotional intelligence at MTs Al-Hidayah Donowarih Karangploso. This study uses a type of quantitative research. The hypothesis test uses a simple linear regression test. The results of this study found that there was an effect of the morning habituation program on increasing emotional intelligence. This is taken from a significant result of 0.000, which is less than the probability value of 0.05, which is concluded that  rejection and acceptance mean that the discovery of the influence of the morning habituation program on the improvement of emotional intelligence of MTs Al-Hidayah students.